Cell sources for trachea tissue engineering: past, present and future. (November 2012) - He, Xiaomin; Fu, Wei; Zheng, Jinghao
Trachea tissue engineering has been one of the most promising approaches to providing a potential clinical application for the treatment of long-segment tracheal stenosis. The sources of the cells are particularly important as the primary factor for tissue engineering. The use of appropriate cells seeded onto scaffolds holds huge promise as a means of engineering the trachea. Furthermore, appropriate cells would accelerate the regeneration of the tissue even without scaffolds. Besides autologous mature cells, various stem cells, including bone marrow-derived mesenchymal stem cells, adipose tissue-derived stem cells, umbilical cord blood-derived mesenchymal stem cells, amniotic fluid stem cells, embryonic stem cells and induced pluripotent stem cells, have received extensive attention in the field of trachea tissue engineering. Therefore, this article reviews the progress on different cell sources for engineering tracheal cartilage and epithelium, which can lead to a better selection and strategy for engineering the trachea.